Ethical Issues and Insecurity in Africa: The Media Dimension - Aondover Eric Msughter; Martha Msoo Hile; Suleiman M. Yar’Adua (Budapest International Research and Critics University, 2023)
This paper addresses ethical issues and the challenges of insecurity in connection to mass media and journalistic practice in the context of Africa. In communication studies, ethics is central and critical to the issue of insecurity in Africa, especially to the credibility in the gathering, processing, and delivery of information for believability. Insecurity constitutes a major impediment to the development of Africa. There are multiple points of violent conflicts, acts of terrorism, kidnapping, and crimes. Many countries in Africa are faced with threats ranging from armed banditry, cattle rustling, armed and sea robberies and piracy, militancy, cultism, pipeline vandalism, illegal oil bunkering, and crude oil theft, illegal refining of petroleum, herdsmen-farmers clashes, activities of IPOB and other separatist groups. All of these make society tense, dangerous, and conflict-ridden with implications on journalism, its ethical practice, performance, and credibility. For an individual or people to internalize, accept, believe and actualize the content of information, such an individual or people must adjudge the source and content of the information based on truthfulness, competence, dynamism, and relevance. Often time, the challenges of insecurity in Africa are accelerated due to the way media handle such issues. When an individual is sufficiently and ethically informed, he or she becomes knowledgeable on a particular subject and the mind is freed from uncertainty, liberated from ignorance, and empowered to effectively participate in the process of national development. The growth and development of Africa have continuously failed to correlate with the quantum of resources allegedly expanded over time. Within this context, this paper examines ethics in journalistic engagement and the issues of insecurity in Africa.